On the fundamental absorption of amorphous semiconductors - Angulo Abanto, José Rubén (2016)
The present thesis reviews different models that describe the fundamental absorption of amorphous semiconductors. These models make use of the electronic density of states to shape the absorption coefficient in the fundamental absorption region. The study focuses on the optical absorption of hydrogenated amorphous Silicon (a-Si:H), hydrogenated and non-hydrogenated amorphous silicon carbide (a-SiC:Hx), and silicon nitride (a-SiN) thin films. On the one hand, parameters like the Tauc-gap and Urbach energy are obtained from the absorption coefficient using the traditional models. On the other hand, a recently proposed model based on band thermal fluctuations was assessed [1]. This model allows a determination of the mobility gap and the Urbach energy from a single fit of the absorption coefficient without the need of identifying the Tauc region beforehand. Furthermore, it is able to discriminate the variation of the Urbach energy from the bandgap. The results allow the evaluation of the aforementioned parameters with annealing treatments at different temperatures. The mobility edges are insensitive to the structural disorder by at least one degree lower than the Urbach energy. This work demonstrates that it is possible to obtain the mobility edge through this model. In addition, the measured Tauc-gap and Urbach energy exhibit a strong linear correlation following the Cody model for all three materials. Finally, the Urbach focus concept is evaluated and estimated under different analysis.